Effectiveness of Virtual Reality Vs Standard Physical Therapy on Range of Motion, Pain and Enjoyment in Patients with Acute Burns: A Meta-Analysis and Evidence Based Review - Hajela, Nupur; Dobson-Brazier, Mercedes; Bea, Jenna Sawdon (Archives of Clinical and Biomedical Research, 2022)
Background: Each year 1.1 million people report having a burn injury, with 45,000 people requiring hospitalization. Patients suffering from a burn, experience one of the most excruciating types of pain, that is most commonly unsuccessfully treated though analgesics. Physical therapy increases a patient’s pain thus decreasing a patient’s compliance with treatment and willingness to move. Virtual reality has been proven to decrease burn pain, but there is limited information on the effects it has on range of motion and treatment enjoyment. The purpose of this study is to determine the effectiveness of VR as a treatment tool to increase ROM and enjoyment as part of cognitive distraction while decreasing reported pain when compared to standard physical therapy in patients with acute burns. Methods: The search between Science Direct, Cinahl and PubMed yielded a total of 242 articles in total which were reviewed based on relevance of titles and abstracts. Prior to reviewing abstracts there were 77 duplicates removed, leaving 165 non-duplicate articles. There were 131 articles removed after reading the abstract and finding the articles did not fit within the meta-analysis leaving 34 articles left to review for inclusion/exclusion criteria. After reviewing the articles, 8 studies eligible for this metaanalysis based on the inclusion and exclusion criteria were analyzed though Microsoft Excel. The studies were used for the following three outcome measures: range of motion, pain and enjoyment. Results: Range of motion presented with homogenous results with a grand effect size of 0.19. Pain was found to have homogeneity with grand effect size of -0.45. Enjoyment was the only outcome measure that presented with heterogeneity and a grand effect size of 1.30. Virtual reality was proven to be an effective way to decrease pain and improving enjoyment. Range of motion had a trend to favoring virtua